New palaeomagnetic results from the Oslo Graben, a Permian Superchron lava province - Haldan, M.M.; Meijers, M.J.M.; Langereis, C.G.; Larsen, B.T.; Heyer, H. (Geophysical Journal International, 2014)
We have performed an extended palaeomagnetic study of the Oslo Graben volcanics, compared to the study of half a century ago by van Everdingen, using modern techniques and a four times larger amount of sites, plus additional rock magnetic experiments. We conclude that the average direction ( D = 204.0, I = −37.9, k = 46.9, α 95 = 2.0) and associated palaeomagnetic pole ( λ = 48.3, φ = 155.5, K = 52.2, A 95 = 1.9) of the Krokskogen and Vestfold volcanics together are statistically identical to those of the earlier study. This gives confidence in the fact that older palaeomagnetic studies can be reliable and robust, even though methods have improved. Our larger number of samples, and better age constraints, enable us to separate the data into two major intervals: the younger, on average, Krokskogen area and the older Vestfold area. The results show firstly that palaeolatitudes are slightly higher than predicted by the latest apparent polar wander path (APWP) for Eurasia by Torsvik et al. These data support an early Permian Pangaea A configuration and do not necessitate a Pangaea B configuration. The larger data set also allows us to assess the distribution of the characteristic remanent magnetization directions of the Oslo Graben in terms of geomagnetic field behaviour, which were acquired during a long period of dominantly single polarity the Permo-Carboniferous Reversed Superchron (PCRS). The distributions show a significantly lower virtual geomagnetic pole (VGP) scatter at the observed (low) latitudes than expected from a compilation from lavas of the last 5 Myr. The data do however show excellent agreement with the scatter observed both during the Cretaceous Normal Superchron and the PCRS. A comparison of the directional distributions in terms of elongation is less discriminating, since the large errors in all cases allow a fit to the predicted elongation/inclination behaviour of the TK03.GAD model.